The Pentagon's New Map : War and Peace in the Twenty-First Century - Barnett, Thomas P. M. (New York The Berkley Publishing Group, 2005)
Military strategist Barnett provides a cutting-edge approach to globalization that combines security, economic, political, and cultural factors to predict and explain the nature of war and peace in the twenty-first century. Building of the works of Thomas L. Friedman and Francis Fukuyama, and then taking a leap beyond, this book offers hope at a crucial yet uncertain time in history.--From publisher description.
Include Notes,Map and Index
Keywords: United States -- Military policy. -- World politics -- 1989- -- Military policy